Implementasi Outdoor Study Method Pada Mata Kuliah Ekonomi Koperasi: (Studi kasus pada Mahasiswa Pendidikan Ekonomi STKIP PGRI Bandar Lampung) - Fitria, Nur (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This study was conducted with the aim of knowing, explaining and analyzing the implementation of or field observation learning methods in the Cooperative Economics course aimed at students of Economics Education STKIP PGRI Bandar Lampung by directly observing the operational processes of cooperative institutions in the city of Bandar Lampung. The sample of this study was all fourth semester Economics Education students who took the Cooperative Economics course with purposive sampling provisions. The research data were in the form of quantitative and qualitative data. The results of the study showed that students' understanding process skills increased with the observation method that directly went into the field to observe the operational processes of cooperative institutions in Bandar Lampung. Student learning activities increased because with the observation method students felt they could increase their knowledge and direct experience in the field and many students gave positive responses to the application of this observation method. Thus, the application of the observation method has a significant effect on improving student understanding and student learning activities on the main material in the Cooperative Economics course.